Reflections on the emergence and evolution of a scholarship of teaching and learning community of practice within a research-intensive higher education context - Dzidic, P.; Castell, E.; Roberts, L.; Allen, Peter; Quail, M. (2017)
In this chapter we present a critical case study analysing the emergence and evolution of a higher education Community of Practice (CoP) centred on the Scholarship of Teaching and Learning (SoTL). This CoP exists in the context of an institution attempting to re-position itself as ‘research intensive’, where there are ongoing tensions between research and teaching, with prevailing perceptions that research is more valued than teaching, and disciplinary research is more valued than teaching and learning research. The chapter draws on the findings from a workshop with the CoP members, conducted within a Futures Studies anticipatory action-learning framework, and analysed using Causal Layered Analysis. Findings highlighted the importance of social context. Three themes emerging from the workshop were members’ perceived systemic exclusion from the wider research community, exploration and contestation of dominant university culture and values, and perceptions that teaching and SoTL are undervalued within the university setting. Individual and collective experiences of exclusion and othering prompted a movement of defiance, fostering the development of a CoP which, over the first 3 years of operation, has achieved institutional recognition, access to resources, competitive research funding success, significant publication outputs, and, growth and stability in research group membership. Multidisciplinary engagement and focus, the research group’s interpersonal style which is based on mutual respect and support, and flexibility through empathy have fostered successes. Ultimately the success of a CoP is not determined by tangible outputs alone. Rather, it is characterised by equity, collaboration, genuine participation and empowerment.